Content and Language Integrated Scientific Modelling: A Novel Approach to Model Learning - Roth, Tamara; Scharfenberg, Franz-Josef; Bogner, Franz X. (Frontiers in Education, 2022)
The relevance of English language competencies in authentic, discipline-specific contexts at school is increasingly acknowledged outside of English-speaking countries. Since any understanding of complex scientific problems requires the combination of scientific literacy with other competencies, such as scientific modelling, the appropriate application of Content and Language Integrated Learning (CLIL) is of great importance. The present study focuses on an established, hands-on outreach genetic education module on DNA structure, which it extends with a bilingual adaption to examine the influence of non-CLIL and CLIL learning on students’ scientific modelling skills and model understanding. When comparing non-CLIL learners (n = 149) and CLIL learners (n = 316), the former received higher scores in the assessment of model-related self-evaluation sheets and built better models. We also found that non-CLIL learners achieved better temporary knowledge of “DNA as a model” scores and, for model evaluation, were more reflective in determining similarities and differences between their hand-crafted model and a commercial DNA school model. However, CLIL learners performed better in comparing their model sketches with their hand-crafted models. They also used different approaches to develop models and conceptualize integral components of models, as reflected in their advanced model understanding. We conclude that CLIL influences modelling qualities on different levels, by fostering modelling practice and, in particular, model understanding.